Proposed Marketing Strategy for Prama Grand Preanger Hotel Bandung (The Indonesian Journal of Business Administration, 2021)
Prama Grand Preanger is one of the Heritage hotel in Bandung owned by Aerowisata Hotels & Resorts. There are two methods that used in the study, qualitative and quantitative method. secondary data are collected from Prama Grand Preanger Hotel, researching books, journals, previous research related to the research, and group discussion. Data collection by distributing questionnaires to 105 respondents. External analysis using General Environment, Industrial Environment, customer analysis, competitor analysis. Internal analysis using 7P Marketing Mix. Based on the interview and questionnaire result, it was found that the hotel problem is lack of promotion. The analysis strategy of Prama Grand Preanger Hotel Bandung through market penetration can be done by increasing marketing efforts, in this case is proposed new 7P Marketing Mix, synergize through Stated Owned Enterprise and Integrated loyalty program. Keyword: Hotel, 7P Marketing Mix, Purchase Intention, Marketing Strategy